Earnings quality, ownership structure and firm performance: Malaysian evidence / Radziah Mahmud - Mahmud, Radziah (Institute of Graduate Studies, UiTM, 2012)
Flexibility in accounting principles allows managers to opportunistically manipulate earnings figure. Accounting scandals around the world provide evidence that earnings manipulation affects the quality and usefulness of reported earnings that will be used by users of financial information to evaluate their investment decisions. Due to imperfect and incomplete market, managers have better information to enable them to engross in the accounting discretion in order to maximise their own interest at the expense of the shareholders. Ownership structure has been acknowledged in the literature as one of the corporate governance mechanisms which can be used to reduce agency and information asymmetry problems. However, the empirical evidence on the influence of ownership structure on firm performance is inconclusive. To address this issue, this study examines whether earnings quality and ownership structure of Malaysian public listed firms are associated with firm performance based on 285 listed firms on the main board of Bursa Malaysia for the period from 2000 to 2007.